Ідентифікація ARS-послідовності флавіногенних дріжджів Pichia guilliermondii - Вороновський, А.Я.; Борецький, Ю.Р. (Биополимеры и клетка, 2000)
An autonomously replicating sequence adjacent to the RfBl gene encoding GTP cyclohydrolase II of the yeast Pichia guilliermondii was identified by transformation experiments. Detailed sequence analysis unveiled two potential ARS elements located 5' and 3' of the RIBI open reading frame. The chromosomal fragment containing the ARS-like sequence 3' to the RIBI structural gene, called PgARS, conferred autonomous replication to hybrid plasmids and high transformation frequencies (104 –105 transformants/ug DNA) in Pichia guilliermondii. Based on the PgARS element a series of E. coli–P. guilliermondii shuttle vectors was developed. Виявлено, що фрагмент хромосомної ДНК Pichia guilliermondii, котрий містить структурний ген GTP-циклогідролази II (RIBІ), у складі рекомбінантних плазмід обумовлює високу частоту трансформації клітин цього виду дріжджів (10⁴–10⁵ трансформантів на 1 мкг ДНК). Показано, що висока частота трансформації і автономна реплікація плазмід у клітинах P. guilliermondii забезпечуються послідовністю (названою PgARS), розміщеною в 3'-області гена RIBІ. Сконструйовано низку рекомбінантних плазмід, котрі є човниковими для бактерій Escherichia coli і P. guilliermondii Обнаружено, что фрагмент хромосомной ДНК Pichia guilliermondii, несущий структурный ген GTP-циклогидролазы II (RIBI), в составе рекомбинантных плазм ид обеспечивает высокую частоту трансформации клеток данного вида дрожжей (10⁴ –10⁵ трансформантов на 1 мкг ДНК). Показано, что высокая частота трансформации и автономная репликация плазмид в клетках P. guilliermondii обеспечивается последовательностью (названной PgARS), расположенной в 3'-области гена RIBI. Сконструирован ряд челночных для Escherichia coli и P. guilliermondii рекомбинантных плазмид.